2014
DOI: 10.1016/j.acap.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Innovative Approaches and Patient-Centered Outcomes From Positive Outliers in Childhood Obesity

Abstract: Objective New approaches for obesity prevention and management can be gleaned from 'positive outliers', i.e., individuals who have succeeded in changing health behaviors and reducing their body mass index (BMI) in the context of adverse built and social environments. We explored perspectives and strategies of parents of positive outlier children living in high risk neighborhoods. Methods We collected up to five years of height/weight data from the electronic health records of 22,443 Massachusetts children, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…12,13 Several children and parents from these focus groups now participate as ongoing members of our parent and youth advisory board. Leaders and staff of youth-serving community-based organizations, including the YMCA, provided critical input on the ideas and activities we ultimately implemented.…”
Section: Intervention Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 Several children and parents from these focus groups now participate as ongoing members of our parent and youth advisory board. Leaders and staff of youth-serving community-based organizations, including the YMCA, provided critical input on the ideas and activities we ultimately implemented.…”
Section: Intervention Developmentmentioning
confidence: 99%
“…We have previously published the methods and results of this formative work. 12,13 Parents reported several practices that facilitated their ability to help their child improve their BMI. Among them were: 1) making changes as a family rather than solely for the child; 2) implementing limits and rules around snacking, screen time and activity, and maintaining consistency around those rules; 3) being involved in the decision-making with their health care provider about their child's weight management; 4) using more immediate rather than long-term outcomes of weight management to motivate change, and 5) maximally leveraging community resources to support behavior change.…”
Section: Intervention Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously suggested that the positive outlier approach may advance progress in childhood obesity by identifying and learning from successful children and families within obesogenic socio-environmental contexts [8]. We have also applied the approach to examine the perceptions and strategies of parents of positive outlier children who have improved their weight status despite living in neighborhoods with high obesity prevalence [9]. …”
Section: Introductionmentioning
confidence: 99%
“…6 In pediatrics, patient-centered approaches positively influence parent satisfaction. 4 Prior qualitative studies using focus groups and interviews have examined pediatric screening, care and communication during the well-child visit from the parent [7][8][9][10][11] or the provider perspective. [12][13][14] To our knowledge, none of these included teens in the discussion to improve well-child visit outcomes.…”
mentioning
confidence: 99%